High critical current density in textured Ba-122/Ag tapes fabricated by a scalable rolling process. (1st April 2015) - Dong, Chiheng; Yao, Chao; Lin, He; Zhang, Xianping; Zhang, Qianjun; Wang, Dongliang; Ma, Yanwei; Oguro, Hidetoshi; Awaji, Satoshi; Watanabe, Kazuo
Abstract : Ag-sheathed Ba0.6 K0.4 Fe2 As2 superconducting tapes were fabricated by a scalable rolling process with high quality precursor. At 4.2 K and 10 T, the critical current density J c is 5.4 × 10 4  A cm −2 . We ascribe the excellent performance to the high purity and homogeneity of the superconducting phase, and the high density and high c -axis texture of the superconducting core. Our method provides a simple way to scale up the production of long-length iron-based superconducting tapes with high J c .